Pertanggungjawaban Pidana Pelaku di Bawah Umur dalam Kasus Pemerkosaan dan Pembunuhan - Clarisa Estefania Simangunsong; Hayyu Nur Anniza; Talitha Ariqa Rahma Irfani; Rahmawati Emma Audrya Agustine; Tiffany Angelita (Jurnal Hukum Lex Generalis, 2025)
The era of globalization facilitates access to information, including negative content that can trigger sexual crimes committed by minors, such as rape and murder. Although Law Number 11 of 2012 on the Juvenile Criminal Justice System regulates sanctions, victims' families consider the penalties which are only half of those for adults to be unjust. This normative juridical research employs a literature study with statutory, conceptual, and case study approaches. The findings indicate that criminal responsibility for offenders under the age of 18 cannot be transferred to their parents, and that current sanctions lack a deterrent effect. It is recommended that the Child Protection Law be reviewed and that harsher penalties be applied to perpetrators.